2021
DOI: 10.1177/14757257211028723
|View full text |Cite
|
Sign up to set email alerts
|

The Misconceptions About Multimedia Learning Questionnaire: An Empirical Evaluation Study With Teachers and Student Teachers

Abstract: In this study, we present the newly developed Misconceptions about Multimedia Learning Questionnaire (MMLQ), we evaluate its psychometric properties (item difficulties, scale reliabilities, and internal structure), and we use it to examine the prevalence of four different misconceptions about multimedia learning in student teachers and teachers. A total of 311 participants (176 teachers and 135 student teachers) responded to the items of the MMLQ. The results revealed moderate reliabilities of the MMLQ scales.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 58 publications
2
33
0
Order By: Relevance
“…Provide feedback first while withholding grades to increase attention to the feedback. Eitel et al (2021) Consider that plausible ideas about learning and the brain might be misconceptions and that science provides insights beyond personal experiences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Provide feedback first while withholding grades to increase attention to the feedback. Eitel et al (2021) Consider that plausible ideas about learning and the brain might be misconceptions and that science provides insights beyond personal experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Given that teachers play a key role in transmitting knowledge and learning strategies to students, it is a promising starting point to assess teachers' knowledge and beliefs about multimedia learning. Eitel et al (2021) examined the prevalence and structure of misconceptions about multimedia learning in teachers and preservice teachers. Developing the Misconceptions about Multimedia Learning questionnaire, they reported that most preservice teachers endorsed three out of four misconceptions.…”
Section: Addressing Teachers' Misconceptions About Self-regulated Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research revealed that the described misconceptions about multimedia learning are highly prevalent among student and in-service teachers. This is especially true for the learning-styles misconception (76-98%; Dekker et al, 2012;Deligiannidi & Howard-Jones, 2015;Dündar & Gündüz, 2016;Eitel et al, 2021;Ferrero et al, 2016;Howard-Jones et al, 2009;Karakus et al, 2015;Krammer et al, 2019;Macdonald et al, 2017;Menz et al, 2020;Papadatou-Pastou et al, 2017;Pei et al, 2015;Simmonds, 2014;Tardif et al, 2015). The hemispheric-isolation misconception is also widely endorsed among these populations (49-89%; Dekker et al, 2012;Deligiannidi & Howard-Jones, 2015;Dündar & Gündüz, 2016;Düvel et al, 2017;Eitel et al, 2019Eitel et al, , 2021Ferrero et al, 2016;Howard-Jones et al, 2009;Karakus et al, 2015;Krammer et al, 2019;Macdonald et al, 2017;Papadatou-Pastou et al, 2017;Pei et al, 2015;Simmonds, 2014;Tardif et al, 2015).…”
Section: Misconceptions About Multimedia Learningmentioning
confidence: 99%
“…Actually, a large part of instruction is based on multimedia material, and teachers often select and prepare multimedia material for their lessons (e.g., McElvany et al, 2012). Yet, prior research has indicated that student and in-service teachers frequently have misconceptions about effective multimedia material (e.g., Dreher et al, 2016;Eitel et al, 2021). Such misconceptions can adversely affect the quality of their instruction and, as a consequence, students' achievement.…”
mentioning
confidence: 99%